Anomalous Right Coronary Artery Originating from Mid Left Anterior Descending Artery- An Unexpected Encounter during Primary Percutaneous Coronary Intervention - Ashwin Tumkur; Dharmendra Kumar Borad (Journal of Clinical and Diagnostic Research, 2022)
The appearance of single coronary artery with anomalous Right Coronary Artery (RCA) originating from left coronary artery is an extremely rare encounter. Here, the authors report one such case of a 34-year-old male, who was serendipitously encountered with a single coronary artery with anomalous RCA arising from mid Left Anterior Descending (LAD) artery. He presented with anterior wall ST-elevation Myocardial Infarction (STEMI) and developed complete heart block. His mid LAD supplying anomalous RCA was totally occluded which was successfully recanalised using drug-eluting stent. The computed tomographic angiography confirmed single coronary artery with anomalous RCA arising from mid LAD across the stent.Thus, if RCA is not seen during traditional coronary angiography, the interventionalist should keep in mind that RCA can originate from LAD.